Study of human structural brain connectivity in healthy aging based on tracts - Pinto, Maíra Siqueira (2018)
The human brain changes in a complex and heterogeneous way throughout life, the normal aging process is associated to significant alterations in the axonal connections. In this study, we evaluated the age-related changes in physical parameters associated with the brain white and gray matter integrity in healthy subjects, as well as the possible correlation between them in specific tracts. Structural images (1 mm isotropic) and diffusion weighted images (2 mm isotropic, b = 1000 s /mm2) of 158 healthy individuals aged between 18 and 83 years were retrospectively collected at the Clinics Hospital of Ribeirao Preto, after their acquisition in a 3T MR scanner. From the structural images, the cortical thickness was estimated and the age effect was evaluated in several regions based on the Atlas of Destrieux. The diffusion-weighted images were processed to characterize the intravoxel diffusion using two models: diffusion tensor (DT) and constrained spherical deconvolution (CSD). Fractional anisotropy (FA) and apparent density of fiber (AFD) maps were estimated and used in statistical group analysis between the three groups separated by age. The most relevant brain tracts were segmented by three procedures: manually, automatically with a specific tool and based on automatic segmented cortical regions. Physical parameters of diffusion (anisotropy and diffusivities) were evaluated in the segmented tracts to determine the age-related changes. The connectome analysis based on two cortical parcellations was performed to evaluate the age effect on characteristic structural brain network parameters. The tract-cortical relationship was evaluated considering the anisotropy of each tract and the thickness of the cortical areas at the end of the corresponding tract. Further analysis was performed to evaluate a possible association of structural and functional connectivity in the corpus callosum (CC). There was significant cortical thinning in 88.5% of the regions during life (p <0.05, corrected for multiple comparisons); the frontal region was the most affected in the initial aging (after 40 years), and the occipital and temporal regions in the elderly (after 60 years). Similarly, the group analysis demonstrated a global pattern of reduction of FA and AFD in the white matter, with a higher rate of degradation of integrity from the sixth decade of life. The manual selection of tracts from the DT model proved to be the most reliable methodology in the precise definition of the tracts for our data. Following this methodology, analysis of anisotropy and diffusion parameters also indicated degeneration of white matter in normal aging in all studied brain tracts and corroborated to the antero-posterior gradient of degeneration in the CC. Fornix was the most affected tract bilaterally, with a 3.5% reduction and an increase of 4% per decade in these parameters, respectively; followed by CC. In the evaluation of the age effect on the connectome estimates, regardless of diffusion model and cortical atlas, there was a decrease in global efficiency, number of connections and local efficiency with aging, mainly in the prefrontal, temporal and parietal and its connections. In the tract-cortical analysis, cortical regions connected by tracts demonstrated similar thinning patterns for the majority of tracts, and a significant relation between mean cortical thinning rate and FA/MD alteration rates were found. In all evaluated tracts, age was the main effect controlling diffusion parameters alterations; there were no direct correlations with cortical thickness for the majority of tracts. Only for the fornix, the values of FA and MD showed significant correlation with the cortical thickness of the subcallosal gyrus in both hemispheres during aging (p <0.05 corrected). For the other tracts, CC, Inferior Longitudinal Fasciculus, Uncinated Fasciculus, Inferior Fronto-occipital Fasciculus, Corticospinal Tract, Cingulum and Arcuate Fasciculus, age was the main effect controlling alterations in the parameters, but there were no direct correlations between FA and MD and cortical thickness during the aging process.